2022
DOI: 10.24251/hicss.2022.585
|View full text |Cite
|
Sign up to set email alerts
|

Fear might motivate secure password choices in the short term, but at what cost?

Abstract: Fear has been used to convince people to behave securely in a variety of cybersecurity domains. In this study, we tested the use of fear appeals, together with threat and coping appraisal components separately and together, on password hygiene behaviors. Fear did indeed elicit the anticipated response: people had higher levels of behavioral intention to engage in better password hygiene. Unfortunately, we also detected a largely negative affective response to the appeals. Fear, as a short-lived emotion, can in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Prior research into cybersecurity and the use of fear appeals by Renaud & Dupuis [81] led us to question whether fear was really being triggered. Dupuis et al [23] found that although fear was indeed triggered, so were other negative emotions. We take this challenge a step further to question: are fear appeals perhaps eliciting a sense of anticipated regret, or even dread, rather than fear?…”
Section: Research Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research into cybersecurity and the use of fear appeals by Renaud & Dupuis [81] led us to question whether fear was really being triggered. Dupuis et al [23] found that although fear was indeed triggered, so were other negative emotions. We take this challenge a step further to question: are fear appeals perhaps eliciting a sense of anticipated regret, or even dread, rather than fear?…”
Section: Research Implicationsmentioning
confidence: 99%
“…Challenges: It is difficult to calibrate the extent of the negative emotion that an appeal can trigger, or the other emotions that arise, and the long-term consequences of these appeals [23].…”
Section: Wielding Emotionsmentioning
confidence: 99%